Successful marketing strategies for martial arts schools (Revista de Artes Marciales Asiáticas, 2025)
This article delves into effective marketing strategies for martial arts schools, with a focus on insights from three successful taekwondo academies in the United States. The information was gathered through interviews with the founders of these schools, followed by an analysis of their strategies using the key marketing principles of STP (Segmentation, Targeting, and Positioning). In this context, successful taekwondo academies are often strategically situated in urban and suburban areas with high foot traffic, fostering strong community engagement and attracting children from middle- and upper-class families who seek discipline as well as family-oriented programs. To enhance enrollment and retention, these schools implement targeted marketing strategies, including premium brand image, social media outreach, and specialized programs that emphasize personal growth, skill development, with a strong emphasis on Asian cultural elements and tradition. By examining these real-world examples, martial arts schools of any style or location may gain practical lessons for attracting and retaining students.